2004
DOI: 10.1161/01.hyp.0000109322.72948.24
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Birth Weight on Blood Pressure and Body Size in Early Adolescence

Abstract: Abstract-The fetal programming theory that birth weight contributes to blood pressure or body size in later life is examined in this study. A prospective longitudinal study was conducted on subjects who were examined as newborns and prospectively interviewed and re-examined at 11 to 14 years old. Low birth weight (Ͻ2500 g) was present in 36% of the sample. The adolescent examination included measurements of blood pressure (BP), both auscultation and oscillometric methods; anthropometrics (height, weight, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 27 publications
3
33
1
1
Order By: Relevance
“…Assim como o verificado no presente estudo, outras investigações não observaram associação inversa entre HAS e peso ao nascer (8,32), corroborando a hipótese de que a ação de fatores pós-natais exerce maior efeito sobre a PA do que os intrauterinos (32,33).…”
Section: Discussionunclassified
“…Assim como o verificado no presente estudo, outras investigações não observaram associação inversa entre HAS e peso ao nascer (8,32), corroborando a hipótese de que a ação de fatores pós-natais exerce maior efeito sobre a PA do que os intrauterinos (32,33).…”
Section: Discussionunclassified
“…Some studies try to overcome this problem using mechanical monitors for physical activity assessment and for further demonstration of the dose-response effect. [28][29][30] However, the problem facing development of rigorous techniques for measuring physical activity is the lack of an ideal standard with which to validate the data, thus making it difficult to truly validate any given technique. Therefore, most of the physical activity studies have been based on questionnaires that have the ability to gather activity information in a short time at low cost.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results were in agreement with that of previous studies, which reported nonsignificant relations of birth weight to SBP among black children and adolescents. 3,6,7 Furthermore, the longitudinal design of our study with upto six repeated measures for SBP could improve power for detecting the differences in SBP among birth weight categories or pubertal stages. 39 Despite these limitations, the present study for the first time examined the role of puberty as a potential effect modifier in the association between birth weight and SBP in children.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, findings of the association between birth weight and SBP during adolescence have been inconsistent. 3 Previous studies have reported inverse, [3][4][5] nonsignificant, 3,6,7 or positive 3,8 associations between birth weight and SBP in early and late adolescence.…”
Section: Introductionmentioning
confidence: 96%